Trehalose-Induced Remodelling of the Human Microbiota Affects Clostridioides difficile Infection Outcome in an In Vitro Colonic Model: A Pilot Study - Buckley, Anthony M.; Moura, Ines B.; Arai, Norie; Spittal, William; Clark, Emma; Nishida, Yoshihiro; Harris, Hannah C.; Bentley, Karen; Davis, Georgina; Wang, Dapeng; Mitra, Suparna; Higashiyama, Takanobu; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Within the human intestinal tract, dietary, microbial- and host-derived compounds are used as signals by many pathogenic organisms, including Clostridioides difficile. Trehalose has been reported to enhance virulence of certain C. difficile ribotypes; however, such variants are widespread and not correlated with clinical outcomes for patients suffering from C. difficile infection (CDI). Here, we make preliminary observations to how to trehalose supplementation affects the microbiota in an in vitro model and show that trehalose can reduce the outgrowth of C. difficile, preventing simulated CDI. Three clinically reflective human gut models simulated the effects of sugar (trehalose or glucose) or saline ingestion on the microbiota. Models were instilled with sugar or saline and further exposed to C. difficile spores. The recovery of the microbiota following antibiotic treatment and CDI induction was monitored in each model. The human microbiota remodeled to utilise the bioavailable trehalose. Clindamycin induction caused simulated CDI in models supplemented with either glucose or saline; however, trehalose supplementation did not result in CDI, although limited spore germination did occur. The absence of CDI in trehalose model was associated with enhanced abundances of Finegoldia, Faecalibacterium and Oscillospira, and reduced abundances of Klebsiella and Clostridium spp., compared with the other models. Functional analysis of the microbiota in the trehalose model revealed differences in the metabolic pathways, such as amino acid metabolism, which could be attributed to prevention of CDI. Our data show that trehalose supplementation remodelled the microbiota, which prevented simulated CDI, potentially due to enhanced recovery of nutritionally competitive microbiota against C. difficile.